2004
DOI: 10.1002/ajmg.b.20125
|View full text |Cite
|
Sign up to set email alerts
|

Alleles of a reelin CGG repeat do not convey liability to autism in a sample from the CPEA network

Abstract: A recent study by Persico et al. [2001: Mol Psychiatry 6:150–159] suggests alleles of a CGG polymorphism, just 5′ of the reelin gene (RELN) initiator codon, confer liability for autism, especially alleles bearing 11 or more CGG repeats (long alleles). The association is consistent across both a case‐control and family‐based sample. We attempted to replicate their finding using a larger, independent family‐based sample from the NIH Collaborative Programs of Excellence in Autism (CPEA) Network. In our data, alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 40 publications
1
39
1
1
Order By: Relevance
“…Several lines of evidence have since provided further support to this model: (1) the association between long RELN alleles and autism, almost entirely carried by Caucasian-American and not by Italian families in our initial study, 4 was independently replicated in two out of three studies assessing also simplex families in North America, [19][20][21] whereas no replication has been reported in European samples recruited in France, the UK, and Germany, 22,23 or in one US-based study assessing multiplex families only; 24 (2) a recent post-mortem study confirms and extends previous findings of decreased Reelin gene expression in autism, 11 reporting coincident changes in Reelin, Dab-1, and VLDL receptor gene expression in frontal cerebral and cerebellar cortices of brains from individuals with autism compared to age-, sex-, and post-mortem interval-matched controls; 25 (3) several epidemiological studies have recently found evidence of prenatal exposure to OP compounds in the USA, particularly for diazinon and chlorphyrifos, which have been most widespread in household use (see Discussion).…”
Section: Introductionmentioning
confidence: 83%
“…Several lines of evidence have since provided further support to this model: (1) the association between long RELN alleles and autism, almost entirely carried by Caucasian-American and not by Italian families in our initial study, 4 was independently replicated in two out of three studies assessing also simplex families in North America, [19][20][21] whereas no replication has been reported in European samples recruited in France, the UK, and Germany, 22,23 or in one US-based study assessing multiplex families only; 24 (2) a recent post-mortem study confirms and extends previous findings of decreased Reelin gene expression in autism, 11 reporting coincident changes in Reelin, Dab-1, and VLDL receptor gene expression in frontal cerebral and cerebellar cortices of brains from individuals with autism compared to age-, sex-, and post-mortem interval-matched controls; 25 (3) several epidemiological studies have recently found evidence of prenatal exposure to OP compounds in the USA, particularly for diazinon and chlorphyrifos, which have been most widespread in household use (see Discussion).…”
Section: Introductionmentioning
confidence: 83%
“…region before the start codon, have reached conflicting results. [43][44][45][46][47][48][49] This may reflect only the common pattern of nonreplication of early claims from small studies 50 or a modest effect may still be present. A large study should be conducted on this association.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies did find an association, [176][177][178] five other studies of comparable size and power did not find an association of the 5 0 UTR trinucleotide or other variants with AD. [179][180][181][182][183] The first positive finding 176 reported an association with the relatively rare longer alleles ( > 10) of the 5 0 UTR trinucleotide polymorphism with AD. However, in another study, 178 the most common repeat 10 was over-represented in AD.…”
Section: Chromosomementioning
confidence: 99%